A SEMIOTIC ANALYSIS OF NOVEL COVERS OF ‘DIARY OF A WIMPY VAMPIRE: BECAUSE THE UNDEAD HAVE FEELINGS TOO’ BY TIM COLLINS - ROHMANIA, DEWI NUR (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: semiotics, sign, myth, novel cover, ‘Diary of a Wimpy Vampire:because the undead have feelings too’. Novel cover contains some signs in the form of verbal and visual to give a clear message about the content of the novel that can be analyzed with semiotics approach. This study applies semiotic study based on Peirce’s typology of sign and Barthes’ mythology. Based on those reasons, this study aims at analyzing: (1) the signs found in both the original cover and the Indonesian version of the first series novel cover of ‘Diary of a Wimpy Vampire: because the undead have feelings too’ by Tim Collins, and (2) the myth built in the novel covers both the original cover and the Indonesian version of the first series novel cover.This study is classified into qualitative research since it is intended to analyze visual and text form. The type of the study is document analysis since it uses novel covers as the source of the data.The study reveals that the iconic signs are used more on the novel covers, both the original cover and Indonesian version than the symbolic and indexical signs. In the point of mythology, those two novel covers illustrate that the main vampire character in this novel is different from the vampire characters in the other vampire novels that are well known before. He has feelings like human being as he experiences love and sadness. The meanings of colors used in those two novel covers also support in building the meaning behind the signs appearing in the novel. It can be concluded that although  there are many signs that are different in both covers, they still build the same myth that is even though the main character of this novel is a blood sucking and immortal, he still has the same feelings like human being in general. Moreover, the original cover also describes the content of the novel more implicitly than the Indonesian one.Through this research, the researcher gives several suggestions for the next researchers to be more sensitive in recognizing the signs as every sign should be described in detail including their meaning and functions. Moreover, they should be  objective in defining and interpreting signs. In addition, the researcher also suggests the next researchers use the application of mythology or different semiotics theories in the other novel cover series of ‘Diary of a Wimpy Vampire’ or other printed media such as album cover and magazine cover.